IL‐36 cytokines and gut immunity. Issue 2 (24th February 2021) - Ngo, Vu L.; Kuczma, Michal; Maxim, Estera; Denning, Timothy L.
Summary: Interleukin 36 (IL‐36) constitutes a group of cytokines that belong to the IL‐1 superfamily. Emerging evidence has suggested a role of IL‐36 in the pathogenesis of many inflammatory disorders. Intriguingly, in the gastrointestinal tract, IL‐36 has a rather complex function. IL‐36 receptor ligands are overexpressed in both animal colitis models and human IBD patients and may play both pathogenic and protective roles, depending on the context. IL‐36 cytokines comprise three receptor agonists: IL‐36α, IL‐36β and IL‐36γ, and two receptor antagonists: IL‐36Ra and IL‐38. All IL‐36 receptor agonists bind to the IL‐36R complex and exert pleiotropic effects during inflammatory settings. Here, we first briefly review the processing and secretion of IL‐36 cytokines. We then focus on the current understanding of the immunology effects of IL‐36 in gut immunity. In addition, we also discuss the ongoing trials that aim to blockage IL‐36R signalling for treating chronic intestinal inflammation and present some unexplored questions regarding IL‐36 research. Abstract : IL‐36 receptor ligands are overexpressed in both animal colitis models and human IBD patients. Depending on the location of expression, the phases, and the disease's context, IL‐36 cytokines can be either favor inflammation or promote the resolution of gut inflammation. In this review, we discuss the current knowledge of IL‐36 biology related to gut inflammation and resolution of intestinal damage and the ongoing clinical trial to block IL‐36R signaling.